Synthesis and Evaluation of N-[5-(Substituted)-1,3,4-Thiadiazole-2-yl] Carbamothioyl Derivatives as Anti-Inflammatory Agents: A Microwave-Assisted Green Chemistry Approach - Shivsharan Dhadde (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study explores the synthesis and anti-inflammatory evaluation of novel N-[5-(substituted)-1,3,4-thiadiazole-2-yl] carbamothioyl derivatives using a microwave-assisted green chemistry approach. The synthesized compounds were characterized through FT-IR, NMR, and mass spectrometry. Their anti-inflammatory activity was assessed using the carrageenan-induced paw edema model in rats, revealing significant efficacy in several derivatives. This approach not only reduced reaction times and energy consumption but also demonstrated the potential of these compounds as therapeutic agents. Introduction: Inflammation is a defense mechanism in response to harmful stimuli, but chronic inflammation can lead to serious diseases. While current anti-inflammatory drugs are effective, they often come with adverse effects, prompting the search for safer alternatives. Thiadiazole derivatives have shown diverse biological activities, including anti-inflammatory properties. This research aims to synthesize N-[5-(substituted)-1,3,4-thiadiazole-2-yl] carbamothioyl derivatives using a green chemistry approach facilitated by microwave irradiation and to evaluate their anti-inflammatory potential. Materials and Method: Analytical grade chemicals were obtained from Sigma-Aldrich. Solvents were purified before use. Using a microwave reactor, equimolar amounts of 5-substituted-1,3,4-thiadiazole-2-amine and thiophosgene were mixed in ethanol and irradiated at 120°C for 10 minutes. The products were purified and characterized using FT-IR, NMR, and mass spectrometry. The carrageenan-induced paw edema model in Wistar rats was used to assess anti-inflammatory activity. Rats were administered synthesized compounds (50 mg/kg) or indomethacin (10 mg/kg) one hour before carrageenan injection. Paw volumes were measured over four hours and analyzed statistically. Results: The microwave-assisted synthesis was efficient, significantly reducing reaction times. Characterization confirmed the structures of the synthesized derivatives. In the anti-inflammatory tests, several compounds showed significant activity, with those having electron-donating groups exhibiting higher efficacy. The statistical analysis demonstrated that the activity of these compounds was comparable to that of indomethacin.